Kombinasi Metode WASPAS dan TOPSIS untuk Menentukan Transportasi Umum (Bus) yang Paling Diminati di Kota Langsa - Afriani, Dina; Hasugian, Abdul Halim (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Langsa City is one of the cities in Aceh province which continues to experience rapid development in various fields, including transportation. Public transportation is an important element in facilitating population mobility, including those who often travel outside the city. People who often travel out of town in Langsa City face a number of problems. Limited accessibility, delays in bus departure and arrival times, as well as lack of service quality such as comfort and facilities, are factors that influence their choice in using bus services. Competitive fares and safety during travel are also important considerations. Therefore, determining the buses that are most popular with people who frequently leave the city in Langsa City is essential to increase efficiency, comfort and passenger satisfaction on long-distance trips. The research findings will provide insight into the most preferred bus transportation based on the criteria applied using the WASPAS and TOPSIS methods. These two methods will later be used to determine the buses that are most popular with the people of Langsa City based on predetermined criteria such as ticket price, distance traveled, passenger capacity, speed and comfort. By using these two methods, it is hoped that we can obtain more accurate and reliable results in determining the public transportation that is most popular with the people of Langsa City.